2019
DOI: 10.1016/j.ymthe.2019.07.014
|View full text |Cite
|
Sign up to set email alerts
|

CD8+CD103+ iTregs Inhibit Chronic Graft-versus-Host Disease with Lupus Nephritis by the Increased Expression of CD39

Abstract: Many patients with systemic lupus erythematosus (SLE) have lupus nephritis, one of the severe complications of SLE. We previously reported that CD8+CD103+ T regulatory cells induced ex vivo with transforming growth factor β (TGF-β) (iTregs) inhibited immune cells responses to ameliorate excessive autoimmune inflammation. However, the molecular mechanism(s) underlying the role of these CD8+ iTregs is still unclear. Here we identified that CD39, which is highly expressed on CD8+ iTregs, cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…The defining markers of CD8 iTregs are still under study and more research will be necessary to reach a consensus [78]. CD8 iTregs have been reported to engage in multiple cell-dependent and independent mechanisms to mediate immune suppression and homeostasis [79][80][81][82][83]. Using mice that were unable to generate both CD4 and CD8 iTregs, Beres et al showed that iTreg-deficient mice had increased expansion of alloreactive T cells, and that CD8 iTregs in the absence of CD4 iTregs had the capacity to prevent GVHD severity [77].…”
Section: Cd8 Itregsmentioning
confidence: 99%
“…The defining markers of CD8 iTregs are still under study and more research will be necessary to reach a consensus [78]. CD8 iTregs have been reported to engage in multiple cell-dependent and independent mechanisms to mediate immune suppression and homeostasis [79][80][81][82][83]. Using mice that were unable to generate both CD4 and CD8 iTregs, Beres et al showed that iTreg-deficient mice had increased expansion of alloreactive T cells, and that CD8 iTregs in the absence of CD4 iTregs had the capacity to prevent GVHD severity [77].…”
Section: Cd8 Itregsmentioning
confidence: 99%
“…Various suppressor cells including mesenchymal stem cells (MSCs) and regulatory T cells (Treg) have been widely considered as a new treatment tool for autoimmune diseases, 78,79 such as graft-versus-host disease (GvHD), [80][81][82] systemic lupus erythematosus (SLE), 83,84 allergic diseases, 85,86 type I diabetes, 87 and multiple sclerosis (MS). 88,89 Particularly, the properties of increasing the ratio of Treg/Th17, as well as differentiating into osteoblasts and chondrocytes, are significant for RA treatment.…”
Section: Cell and Cell Derivatives Deliverymentioning
confidence: 99%
“…Meanwhile, it has been established that adenosine can inhibit the advancement of renal fibrosis through a combination of A2A and A2B receptors on renal tubular endothelial cells. 31 Treg cells or macrophages were involved in renal protection mediated by CD39, 32,33 even though the macrophages were also one of the main inflammatory cells in kidney injury. Overexpression CD39 fails to protect against renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%